Evaluation of Knowledge and Practice Toward Cystic Fibrosis Disease Among Medical Students and the Residents of Western Libya (Razi Medical Journal, 2025)
Cystic fibrosis (CF) is the most common severe autosomal recessive disorder worldwide, affecting an estimated 162,428 individuals. The incidence in Libya remains unknown due to limited diagnostic capacity, particularly the lack of sweat test facilities. Public and professional awareness are essential for early detection and management. This study aimed to evaluate the level of CF awareness among residents of Western Libya, identify potential knowledge gaps, and provide baseline data for future awareness programs. A cross-sectional survey was conducted among the general public and medical students in western Libya. A 17-item questionnaire, developed in English and translated into Arabic, was distributed both electronically and in print. Items assessed CF knowledge, attitudes, and awareness sources. An additional targeted questionnaire was administered to medical students who are likely to encounter CF patients in their clinical practice. Data were analysed using descriptive statistics and Chi-square tests for associations. Of 485 respondents, 340 (70.1%) had heard of CF, primarily via the internet/media (55%). Knowledge levels were moderate overall, with females scoring higher than males. Awareness varied by gender and age but showed no significant difference across other demographic groups. Participants demonstrated positive attitudes toward CF, including informed marital decisions, indicating an understanding of its genetic nature. However, substantial knowledge gaps were identified among both the general public and medical students. Although attitudes toward CF were generally positive, awareness remains insufficient in western Libya, even among future healthcare providers. Targeted educational initiatives are necessary to enhance knowledge, facilitate earlier diagnosis, and improve patient outcomes.
Keywords: Cystic Fibrosis, Knowledge and Practice, Medical Students, Public.